FACTORS LEAD TO DEPRESION DURING ANTENATAL CARE EVERY TRIMESTER OF PREGNANT MOTHER - Surya Kurniawan, Eddy; Ratep, Nyoman; Westa, Wayan (E-Jurnal Medika Udayana, 2013)
The most important factor in reducing maternal and infant mortality rates began during pregnancy. In 2000, one in twenty children die before reaching the age of five years and a mother died of childbirth out of every 325 live births. The death rate in research mainly indicated comparable levels of depression due to stress in pregnant women. The occurrence of symptoms of depression during the perinatal period can be easily recognized. Depression during pregnancy is a common mood disorder such as depression that occurs in the laity in general, where the incidence of depression will occur chemical changes in the brain. Each trimester of pregnancy are at risk of psychological disorders respectively. Antenatal care plays a very important for the safety of the mother and fetus, minimizing the risks of pregnancy, and reduce the number of neonatal deaths. Nursing antenatal care should have run in accordance with minimum standards for pregnant women to obtain a safe childbirth and satisfying.
Keywords: depression, antenatal